Analisis Dan Perancangan Aplikasi Chatting (DChat) Pada Rumah Sakit Umum Permata Hati Berbasis Mobile - Jaya, I Nyoman Wiratma; Mastrika Giri, Gst. Ayu Vida (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2019)
The development of information technology has a very rapid impact on the development of human activities, one example is the application of information technology in the form of information systems at the Permata Hati Klungkung general hospital. The information system helps hospital management to record every transaction that occurs at the hospital. But one of the problems that occur at Permata Hati Klungkung General Hospital is the limited communication and transactions between the pharmacist and the cashier because the cashier is located on the second floor of the hospital while the pharmacist is on the first floor of the hospital, so that the cashier must go down to the first floor to give the prescription pharmacist, it is very draining time and energy, so the solution to the problem is to build a chat application called DChat as a medium of communication between cashiers and pharmacists. This application can be used to send text and picture messages. The DChat application is built using framework react native with the backend of php and MySql database.